1977
DOI: 10.1017/s0022215100084802
|View full text |Cite
|
Sign up to set email alerts
|

Facial nerve schwannoma

Abstract: The present article gives a brief and complete account of the incidence, pathology, clinical features, diagnosis, management and prognosis of the schwannoma with special reference to facial nerve schwannomas. A case report of a rare schwannoma of the vertical part of the facial nerve found on biopsy of tissue during a postaural modified radical mastoidectomy is included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They include deafness, ageusia, reduced lacrimation and signs of intra-cranial space occupation. The most common presenting feature is facial weakness or paralysis, occurring with a frequency of 100 per cent (Curtin and Lanigan, 1964;Isamat et al, 1975;Anand et al, 1977;Liliequist, 1978;Baur and Greisen, 1984;Jung et al, 1986) in most reported series. Murata et al, (1985) quote a frequency of facial paresis of just over 90 per cent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They include deafness, ageusia, reduced lacrimation and signs of intra-cranial space occupation. The most common presenting feature is facial weakness or paralysis, occurring with a frequency of 100 per cent (Curtin and Lanigan, 1964;Isamat et al, 1975;Anand et al, 1977;Liliequist, 1978;Baur and Greisen, 1984;Jung et al, 1986) in most reported series. Murata et al, (1985) quote a frequency of facial paresis of just over 90 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…Facial nerve schwannomas are relatively rare tumours with 183 cases having been reported (Curtin and Lanigan, 1964;Stewart, 1966;Hoshino and Paparella, 1970;Isamat et al, 1975;Anandera/., 1977;Liliequist, 1978;Murataef a/., 1985;Jung et al, 1986). A slowly progressive facial palsy is the predominant feature in such cases and the role of surgical exploration of the nerve, for diagnostic purposes and removal of the tumour, has been stressed (Stewart, 1966;Isamat et al, 1975;Anand et al, 1977;Murata etal., 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Repeated fine-needle aspiration biopsy may not always contribute to a correct preoperative diagnosis, and the tumor is sometimes identified only intraoperatively. 6 Facial schwannomas located in the labyrinthine portion of the facial nerve or at the geniculate ganglion show specific clinical and radiologic manifestations that can be distinguished from tumors of other portions of the nerve, petrous bone area, or the cerebellopontine angle. 7 However, a facial nerve schwannoma of unusual size in the temporal bone is one of the rare manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…In two large series of brain tumors in children, there were no cases of schwannomas reported [2,4], Facial nerve schwannomas are even a more unusual occur rence; since the first reported case in 1930 in a 16-year-old girl, 103 cases had been reported for all ages in the world literature [1,3,5,7,8]. The age occurrence was reviewed in 38 cases in which information of the first symp toms was known and only in 12 cases were reported under the age of 20.…”
mentioning
confidence: 99%